2007
DOI: 10.1159/000105546
|View full text |Cite
|
Sign up to set email alerts
|

Current Status and Clinical Applications of Cardiac Multidetector Computed Tomography

Abstract: Contrast-enhanced multidetector-row computed tomography (MDCT) is now capable of providing high-quality noninvasive views of cardiac anatomy and ‘instant’ noninvasive coronary angiography. With current generation 64-slice scanners, MDCT can be performed in most patients with minimal patient discomfort and high diagnostic accuracy. MDCT may obviate the need for invasive diagnostic angiography in patients with borderline symptoms or equivocal noninvasive testing. It is useful in assessing the symptomatic patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
2

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 223 publications
0
10
0
2
Order By: Relevance
“…Moreover, cardiac CT provides morphological information and facilitates the evaluation of global and regional cardiac function (cardiac valves, perfusion, and vitality) [6][7][8]. Numerous scientific articles published in recent years testify to the intense research activities in the field of cardiac CT [5,[9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, cardiac CT provides morphological information and facilitates the evaluation of global and regional cardiac function (cardiac valves, perfusion, and vitality) [6][7][8]. Numerous scientific articles published in recent years testify to the intense research activities in the field of cardiac CT [5,[9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] A recent study has demonstrated how much the latest improvement in MDCT technology with a faster gantry rotation time and submillimeter slices acquired with 64-slice CT scanners has led to an increase in segments of the coronary tree being evaluable for the detection of coronary artery stenosis. MDCT has been shown to be a reliable diagnostic technique for the evaluation of coronary artery stenoses.…”
Section: Discussionmentioning
confidence: 99%
“…MDCT has been shown to be a reliable diagnostic technique for the evaluation of coronary artery stenoses. [10][11][12][13] However, coronary calcification influences image quality, and blurring due to severe calcification can cause an image to be uninterpretable. [14][15][16][17][18] Furthermore, MDCT tends to overestimate the degree of stenosis compared with that of CCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advent of multidetector-row systems has made CT study of the heart possible, despite the heart's involuntary motion and complex anatomy, which have been the main hurdles for noninvasive cardiac imaging [3][4][5]. The use of cardiac synchronisation techniques and pharmacological agents for slowing the heart rate have in fact enabled the reduction of pulsatility artefacts and the attainment of submillimetre volumetric data sets of good diagnostic quality in any phase of the cardiac cycle [2,4].…”
Section: Introductionmentioning
confidence: 99%